Lossless segmentation of Brain Tumors from MRI images using 3D U-Net - Farha, Ramisa; Nuha, Nigar Sultana; Sakib, Syed Nazmus; Rafi, Sowat Hossain; Khan, Md Sabbir (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.